2012
DOI: 10.5114/pjp.2012.32772
|View full text |Cite
|
Sign up to set email alerts
|

Allicin has significant effect on autoimmune anti-islet cell antibodies in type 1 diabetic rats

Abstract: The research purpose was to experimentally investigate the effect of allicin administration on the levels of main type 1 diabetes (IDDM) autoantibodies which are antiislet cell antibodies (ICA) with an attempt to find a relation between this immunological effect and histological and/or biochemical findings. We have evaluated, with the help of ELISA kits, the levels of ICA and serum insulin in male Sprague-Dawley rats with Streptozotocin-induced IDDM in addition to pancreatic histological findings. The four gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Additionally, the diabetic group showed an increase in diuresis, creatinine clearance, proteinuria, glycosuria and urinary excretion of NAG, which are considered as hallmarks of renal dysfunction in diabetes. These results are in good agreement with other studies, which reported proteinuria or albuminuria in this experimental model of diabetes [ 3 , 11 , 12 , 15 ]. It has been demonstrated that one month of allicin treatment prevented the loss of body weight in diabetic animals.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, the diabetic group showed an increase in diuresis, creatinine clearance, proteinuria, glycosuria and urinary excretion of NAG, which are considered as hallmarks of renal dysfunction in diabetes. These results are in good agreement with other studies, which reported proteinuria or albuminuria in this experimental model of diabetes [ 3 , 11 , 12 , 15 ]. It has been demonstrated that one month of allicin treatment prevented the loss of body weight in diabetic animals.…”
Section: Discussionsupporting
confidence: 93%
“…Diallyl thiosulfinate (allicin) is a major component formed when garlic ( Allium sativum ) is crushed or ground [ 8 ]. Allicin is considered as a panacea as it has a broad spectrum of physiological activities such as antihypertensives [ 9 , 10 ], antioxidants [ 9 ], antidiabetics [ 11 ], cardioprotectives [ 10 ], nephroprotectives [ 11 ], and immunomodulators [ 12 , 13 ]. As far as nephroprotective mechanisms of allicin in experimental DN are concerned, recent studies have shown that this garlic derivative partially reverses the increased expression of transforming growth factor β (TGF-β) and the activation (i.e., phosphorylation) of its downstream target extracellular signal-regulated kinase ½ (ERK1/2) that drive renal epithelial-mesenchymal transition and fibrosis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Albajali et al (2011) reported that the aqueous extract of A. sativum increased the diameter of pancreatic islets in STZ-induced diabetic rats. In another study, intraperitoneal injection of A. sativum oil decreased beta cell degeneration and level of anti-islet antibodies in the animals with T1D (Osman et al, 2012). Alashkham et al (2013) also showed regenerative action of this oil in the pancreatic islets of diabetic rats.…”
Section: Allium Sativummentioning
confidence: 94%
“…Allicin is the major active component of A. sativum and a precursor of many secondary compounds formed in crushed garlic preparations or aged garlic. This compound has been proposed to be responsible for the health promotion benefits of A. sativum and protective actions in pancreatic islets (Osman et al, 2012).…”
Section: Allium Sativummentioning
confidence: 99%
“…In addition, allicin may stimulate the immune system to release more active factors, which could inhibit the growth of tumor cells through enhancement of its anticancer effects (3,7). As compared with traditional chemotherapy drugs, in the clinical treatment of tumors allicin not only has no toxic effects on the body, but may also stimulate the body to release various cytokines and enhance immune resistance (5,9).…”
Section: Introductionmentioning
confidence: 99%